Green process innovation and financial performance: The role of green social capital and customers' tacit green needs - Xuemei Xie; Thu Thao Hoang; Qiwei Zhu (Journal of Innovation & Knowledge (JIK), 2022)
As environmental concerns continue to gain greater importance, green process innovation has been recognized as a crucial strategy for firms to enhance their financial performance. Yet, it has not been clarified how companies can reduce risks and effectively use resources at different levels of green process innovation. Based on data from 221 Chinese manufacturing firms collected via the survey method, we address this research gap by examining the effects of different levels of green process innovation on firms' financial performance by focusing on the moderating roles of green social capital and customers' tacit green needs. We find that green process innovation has a U-shaped impact on firms' financial performance, such that the impact is initially negative but then becomes more positive as the level of green process innovation increases. We also find this U-shaped relationship is moderated by green social capital and green needs' tacitness, such that green social capital weakens the negative effect of green process innovation on firms' financial performance, whereas green needs' tacitness strengthens the negative effect of green process innovation on firms' financial performance. Our findings contribute to the literature on green innovation by highlighting the nonlinear relationship between green process innovation and firms' financial performance. This research also offers more fine-grained insight into the contingent mechanisms of green social capital and green needs' tacitness, as well as how firms' engagement with green process innovation can have profound effects on their financial performance. Our results provide important implications for managers regarding the financial benefits of green process innovation that is achieved by leveraging the roles of green social capital and green needs' tacitness.
Keywords: 650; Financial performance; Green needs' tacitness; Green process innovation; Green social capital